Citizenship education courses are used as a means of implementing multicultural education at the Politeknik Pelayaran Sorong - Permady, Gigieh Cahya; Zulfikar, Gilang; Siswanto, Siswanto; Nanggala, Agil (Univeritas Papua, 2023)
The importance of intercultural education in vocational education motivates this study. This study aims to give a